Advanced Squamous Cell Carcinoma of the Tongue in an Elderly Patient: A Clinical and Histopathological Case Report - Azenha, Marcelo Rodrigues; Watanabe, Plauto Christopher Aranha; Forero, Brenda Pattigno; Bueno, Renan de Barros e Lima; Loureiro, Kléber Augusto; Leon, Jorge Squiche (Brazilian Journal of Case Reports, 2025)
Squamous cell carcinoma of the tongue is a highly aggressive malignancy that frequently presents in advanced stages, especially in elderly patients. This report describes a case of an 81-year-old male with a large lesion of the tongue, focusing on the clinical presentation, anatomical considerations, diagnostic approach, histopathological analysis, and definitive surgical management. A detailed discussion examines the complexity of treating squamous cell carcinoma of the tongue, including its etiology, clinical behavior, treatment challenges, and the impact on geriatric patients. The case emphasizes the importance of multidisciplinary care and early diagnosis to optimize outcomes in such aggressive and extensive oral cancers.